Design and development of motorcycle helmet using carbon fiber reinforced epoxy resin hybrid composite - Nuzhat Aqila Tushe; Syed Tanjib Mahmud; Nafiul Islam; Golam Mostofa; Noshin Tasnim Tuli; Adib Bin Rashid (Results in Materials)
Motorcycle helmets are crucial for rider safety, and there's a high need for affordable helmets that provide optimal safety to the riders. This research focuses on manufacturing motorcycle helmets by applying carbon fiber, Kevlar, and fiberglass reinforced with epoxy resin. Carbon fiber helmets provide durability, comfort, and affordability. Kevlar is lightweight, offers excellent ballistic protection, reduces fatigue, and is resistant to certain threats, whereas fiberglass is strong and resists bending and compression. This research aims to design a motorcycle helmet following the regulations provided by the Department of Transportation (DOT). Samples with different stacking sequences, sample A (CFCFC), sample B (FCFCF), and sample C (FCKCF), were fabricated with a 3 mm thickness and tested for tensile strength, flexural bending, and impact to ensure the efficacy of the helmet. After analyzing the results, it was observed that in the tensile test, sample B achieved the highest tensile strength (124.7 MPa), followed by sample A (89.78 MPa) and sample C (59.01 MPa). In the flexural test, sample A demonstrated a remarkable flexural strength of 0.767 MPa and a flexural modulus of 6.60 MPa, which is much higher than sample B and C. The results indicate that the arrangement of the reinforcement fibers in composite materials plays a vital role in determining the flexural strength and modulus exhibited by the composites. In the impact test, sample C, incorporating Kevlar fiber, demonstrated the highest impact energy absorption, followed by samples A and B. This trend can be attributed to the inherent properties of Kevlar fiber, which possesses a notably higher capacity to absorb energy when subjected to high forces. With scanning electron microscope (SEM), the structural morphology of hybrid composites is examined to understand the complex microstructures and interfaces present in the composite materials.